(untitled) (International Journal of Engineering and Computer Science, 2015)
For photovoltaic (PV)-battery application, mostly for utility-scale PV-battery application a new converter i.e. Reconfigurable solar converter (RSC) is introduce. The output power of PV module varies with solar irradiation; temperature; loads and it quickly and accurately tracks the sun. The basic concept of the RSC is to employ a single-stage three phase conversion system to perform different operation modes such as dc/dc and dc/ac for solar PV systems with energy storage. This converter solution is appealing for PV-battery application as it minimizes the weight, volume, the number of conversion stages there by reducing the cost, and improving efficiency. In this paper fuzzy logic controller (FLC) is used for controlling the Reconfigurable solar converter (RSC) for photovoltaic (PV)-battery application, mostly for utility-scale PV battery application. The main advantage of fuzzy logic control is to eliminate harmonic content, improve the system response and steady state error.